IMF Survey, Volume 36 Issue 06. (IMF Survey; IMF Survey ;, 2007)
Spring Meetings preview, world outlook, global financial stability, U.S. subprime mortgages, labor globalization, external imbalances, IMF and Africa, wage bill ceilings, policy support instrument, modernizing IMF surveillance, India, Bulgaria, PNoWB.